Peran Kepala Sekolah Untuk Meningkatkan SDM Lembaga Pendidikan Islam - Wirda Hasanah (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The principal has a very important role to improve the quality of the institution he leads. The principal is the person who leads an organization or institution for teaching and learning and a place to receive and give lessons that are responsible to all people they lead. The principal is also very decisive in improving the quality of human resources (HR). Moreover, in Islamic education institution, one of the factors to consider is human resources, namely people or individuals who provide energy, talent, and creativity as well as efforts for the progress of the organization concerned. Therefore, every school is required to always pay attention to these aspects and not just technological and economic aspects in every business.